IoT Storage Optimisation Security Framework Based on a Secure Hash Algorithm - Agnihotri , Aditiya (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The purpose of this research is to examine the risks that IoT applications encounter throughout operational operations, data routing, and energy utilisation, as well as potential solutions to these problems utilising Blockchain technology. This study is broken up into four parts: finding a secure hash technique for the huge volumes of data produced by IoT devices; improving storage; using cluster-based routing to keep out unwanted visitors; and safeguarding IoT programmes. The trust of the blockchain node to existing applications for the Internet of Things cannot be assured, and a sizable amount of communication assets would be used in the process of achieving consensus using the proposed security evolution method of Hybrid Cryptographic Hash Function (HCHF). Private Consensus Bitcoin with Hybrid Cryptographic Hash Function (HCHF) Enhanced Trust on Multilink was a newly developed consensus method in this study. The following are some of the key features of the IoT applications that make use of the suggested HCHF method: 1) The confidence of the nodes in the IoT application grew as a result of the development of the trust attribute mechanism, leading to the formation of a grouping structure within the network. The trust in the system is boosted by the grouping adjustment mechanism. Second, the complexity of communication is considerably simplified by categorising nodes according to their level of trust. The experimental findings show that the system's communication effectiveness and overall trust may be greatly increased by the blockchain's application of the upgraded method.